The Role of Artificial Intelligence (AI) in Developing English Language Skills in the Saudi EFL Context: An Analytical Study (المجلة الدولية للعلوم التربوية والآداب, 2024)
This paper explores the role of Artificial Intelligence (AI) in language learning, examining its impact on language skills. The study synthesises research findings from diverse sources, including academic journals, conference proceedings, and scholarly books, to provide a comprehensive overview of the current state of AI integration in language learning. Key themes addressed include the effectiveness of AI-driven language learning platforms, the role of AI in learning experiences, the potential of AI technologies in language learning. Additionally, the paper discusses challenges and future directions in the field, offering insights for researchers, educators, and practitioners interested in harnessing the potential of AI to enhance language learning outcomes.